UJI AKTIVITAS ANTIBAKTERI EKSTRAK METANOL DAUN KECUBUNG (Datura metel L.) TERHADAP BAKTERI Streptococcus pneumonia DAN Klabsiella pneumonia - A. Mu’thi Andy Suryadi; Moh Adam Mustapa; Faramita Hiola; Sintiya Basiru (Indonesian Journal of Pharmaceutical Education, 2021)
Infectious disease is a disease caused by microbes, including bacteria. One of the microorganisms that often causes infectious disease is Streptococcus pneumoniae and Klabsiella pneumoniae. Based on empirical data, plant that has antimicrobial potential is amethyst leaves (Datura metel L.). This study aims to know the antibacterial activity and concertration of amethyst leaves (Datura metel L.) against Streptococcus pneumoniae and Klabsiella pneumonia. This is an experimental study which includes antibacterial activity test, MIC (Minimum Inhibitor Concertration) test, MFC (Minimum Fungicidal Concertration) test, and bacterial potency test. The finding shows that the antibacterial activity test of amethyst leaves (Datura metel L.) methanol extract is able to inhibit bacterial growth of Streptococcus pneumonia at a minimum inhibitor concertration of 15% and an optimum concertration of 50% with an average of 16.33 mm and 19.30 mm. Meanwhile, for Klabsiella pneumoniae, the minimum inhibitor concertration is 20% and the optimum concertration is 50%, with an average of 13.82 mm and 17.73 mm. this is based on the results of One Way Anova data (a 0.01) with a 99% confidance level.